KANDUNGAN GIZI DAN SERAT PADA TEPUNG GAYAM - Rahayu, Nur Setiawati; Safitri, Debby Endayani; Sulaeman, Ahmad; Setiawan, Budi (ARGIPA (Arsip Gizi dan Pangan), 2024)
Gayam is one of the foodstuffs in the legume group typical of Indonesia, the less varied processing makes gayam less popular. Nowadays, people are starting to consume plant-based foods, because they are considered to have more health benefits. This makes gayam an opportunity to be reintroduced to the wider community. This study aims to analyze the nutritional content of gayam which has gone through the grinding process to see its potential as a local food ingredient that can provide health benefits. This research uses an experimental laboratory study design with a completely randomized design and sample testing is done in duplicate. The result of this study is gayam that has gone through the process of pressing and sieving with a density level of 80 mess has a carbohydrate content of 74.59%, protein 9.49%, fat 3.62% and fiber 13.79%. When compared to other types of flour on the market, such as rice bran flour, corn flour and other legume flour, gayam has a higher fiber content, thus making gayam a potential functional food ingredient.